Salmonella Interaction with and Passage through the Intestinal Mucosa: Through the Lens of the Organism - Hallstrom, Kelly; McCormick, Beth A. (Frontiers in Microbiology, 2011)
Salmonella enterica serotypes are invasive enteric pathogens spread through fecal contamination of food and water sources, and represent a constant public health threat around the world. The symptoms associated with salmonellosis and typhoid disease are largely due to the host response to invading Salmonella, and to the mechanisms these bacteria employ to survive in the presence of, and invade through the intestinal mucosal epithelia. Surmounting this barrier is required for survival within the host, as well as for further dissemination throughout the body, and subsequent systemic disease. In this review, we highlight some of the major hurdles Salmonella must overcome upon encountering the intestinal mucosal epithelial barrier, and examine how these bacteria surmount and exploit host defense mechanisms.